Controversies in the Treatment of Ingrown Nails - Eckart Haneke (Hindawi Limited, 2012)
Ingrown toenails are one of the most frequent nail disorders of young persons. They may negatively influence daily activities, cause discomfort and pain. Since more than 1000 years, many different treatments have been proposed. Today, conservative and surgical methods are available, which, when carried out with expertise, are able to cure the disease. Packing, taping, gutter treatment, and nail braces are options for relatively mild cases whereas surgery is exclusively done by physicians. Phenolisation of the lateral matrix horn is now the safest, simplest, and most commonly performed method with the lowest recurrence rate. Wedge excisions can no longer be recommended